The impact of song-based english lessons in the motivation of EFL students - Vallejo Gudiño, John Sebastian (2025)
Despite decades of research on the motivational impact of songs in English as a Foreign Language (EFL) class-rooms, many educators remain unaware of their potential. This study investigates how EFL learners perceive their learning journey when incorporating song-based lessons. Songs are valuable tools for achieving personal and group language learning goals. They offer a multifaceted approach, encompassing cultural immersion, vocabulary acquisition, enhanced listening comprehension, facilitated grammar application, and the sharpe-ning of various language skills – all presented within a rhythmic structure. Recognizing the impact of music on mood and motivation is crucial. Research in this area is essential to understand how specific songs in-fluence motivation levels. By investigating these effects, educators can choose music that optimizes learning environments and supports students in reaching their academic objectives. Songs are powerful tools in EFL classrooms, providing an engaging approach to language learning on multiple levels. Understanding their im-pact on mood and motivation allows educators to leverage these benefits and enhance the overall learning experience for students.